The Green Marketing Strategy Muscularly Influence on High-performance of Target Sales for Housing Apartment Complex in Malaysia. - Ullah, Md Amanat; wee, Seow Ta (Archives of Business Research, 2016)
The green marketing strategy considers as a marketing strategy with green natural environmental facilities strongly associated with the 4Ps in the property market. The terms green marketing is known as incorporate of the natural green environmental element in marketing strategy. This green marketing directly influences on product, price, place and promotional activities to achieve the target sales. This green marketing is basically appropriate in property marketing because most of the customers want the green environment to reside in the city to get a healthy life. The green environmental elements must intensification of the beauty of product to attract the target customer. Most of the developers applied this policy in their marketing strategy as an effect they achieved the target goals.